2002
DOI: 10.1002/ijc.10683
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hyaluronan synthase 2 or hyaluronidase 1 differentially affect the growth rate of transplantable colon carcinoma cell tumors

Abstract: Advanced colorectal cancers are often associated with elevated amounts of hyaluronan. To investigate the importance of hyaluronan in colon carcinoma tumor progression, we have expressed by stable transfection hyaluronan synthase 2 (Has2) and hyaluronidase 1 (Hyal1) in the rat colon carcinoma cell line, PROb. We found that hyaluronan overproduction led to a higher growth rate of tumor cells in vitro, and to a faster development of transplantable tumors in syngeneic rats, compared to the mock-transfectants. Has2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 48 publications
7
78
0
4
Order By: Relevance
“…It is therefore plausible that the HAS isoforms are involved in different stages of malignant tumor progression. Molecular cloning of the HAS genes enabled us to control HA biosynthesis and investigate HA functions in malignant transformation (23)(24)(25)(26)(27)(28)(29)(30). Overexpression of HAS2 enhanced both the anchorage-independent growth and tumorigenicity of a human fibrosarcoma cell line (24).…”
Section: Ha Is a Linear Polysaccharide Composed Of The Repeating Disamentioning
confidence: 99%
“…It is therefore plausible that the HAS isoforms are involved in different stages of malignant tumor progression. Molecular cloning of the HAS genes enabled us to control HA biosynthesis and investigate HA functions in malignant transformation (23)(24)(25)(26)(27)(28)(29)(30). Overexpression of HAS2 enhanced both the anchorage-independent growth and tumorigenicity of a human fibrosarcoma cell line (24).…”
Section: Ha Is a Linear Polysaccharide Composed Of The Repeating Disamentioning
confidence: 99%
“…Hyaluronidase levels were found to be more elevated in higher-grade cancers or in metastases from breast, brain, prostate and bladder, 3,10 -12 but recent functional studies have shown that hyaluronidase could inhibit growth of grafted tumors and metastases development. [13][14][15] …”
Section: ؊5mentioning
confidence: 99%
“…Hyaluronidase levels were found to be more elevated in higher-grade cancers or in metastases from breast, brain, prostate and bladder, 3,10 -12 but recent functional studies have shown that hyaluronidase could inhibit growth of grafted tumors and metastases development. [13][14][15] Six hyaluronidase-like genes have been described, distributed in 2 clusters on chromosomes 3 (HYAL1, -2, -3 genes) and 7 (PH-20 and the pseudogene HYALP1). 16 Recent data suggest a membrane localization for hyaluronidase-2 17 and a sequential model for HA degradation has been proposed where hyaluronidase-2 (HYAL2) would mediates the first step.…”
mentioning
confidence: 99%
“…The plasma HA concentration of patients with this disorder is 40-90-fold higher than in normal serum. The role of hHyal-1 in tumor progression depends on its cellular concentration; it functions as a tumor suppressor at low or very high concentration and as a tumor promoter at moderate concentration (13,(16)(17)(18).…”
mentioning
confidence: 99%